Analysis of Dietary Compliance on Blood Glucose Level Changes in Diabetes Mellitus Patients - Widianti, Sherly (CV. Literasi Publikasi Indonesia, 2024)
Diabetes is a metabolic disorder characterized by increased blood glucose levels due to impaired insulin production, insulin function, or a combination of both. To date, no cure exists for the disease; current efforts focus on controlling blood glucose levels, one of which is through dietary management. The International Diabetes Federation (IDF) projects that among the top 10 countries with the highest number of diabetes cases, China, India, and the United States occupy the top three positions. Indonesia ranks seventh, with 10.7 million individuals diagnosed with diabetes. It is further estimated that by 2030, the global number of diabetes mellitus cases will increase to 678 million. This underscores Indonesia's significant contribution to the prevalence of diabetes cases in Southeast Asia. A diabetes mellitus diet is specifically designed to help patients achieve and maintain normal blood glucose levels. This study aimed to analyze dietary compliance and its impact on blood glucose level changes in diabetes mellitus patients. A qualitative descriptive research method was employed, conducted at Kenten Permai Public Health Center, Palembang. The qualitative data analysis was inductive, leading to hypothesis development. The study involved three diabetes mellitus patients as informants and one expert informant, a nutritionist. The findings revealed that one respondent was fully compliant with the diet, one was partially compliant, and one was non-compliant. Respondent D, who adhered to the schedule but not the portion sizes or food types, showed a reduction in blood glucose levels from 186 mg/dL to 160 mg/dL. Respondent R, who fully complied with portion sizes, food types, and meal timings, experienced a decrease from 213 mg/dL to 136 mg/dL. Meanwhile, respondent Y, who was less compliant, exhibited only a slight reduction, from 328 mg/dL to 298 mg/dL. All respondents demonstrated awareness of the diabetes mellitus diet and had started implementing it in their daily lives.